A Simulation-Based Kinesthetic Learning Model of Indonesian-Thailand College Students to Prevent Long-Term Musculoskeletal Health Problems in Rural Areas - Ni Luh Dwi Indrayani; I Gede Putu Darma Suyasa; Ni Luh Putu Inca Agustini Buntari; Israfil Israfil; Ni Luh Putu Kamaryati; Ni Putu Dita Ariani Sukma Dewi; Nadya Treesna Wulansari; Ida Ayu Suptika Strisanti; Warongrong Nelson (Ahmar Metakarya: Jurnal Pengabdian Masyarakat, 2026)
Musculoskeletal health problems are among the most common health issues affecting communities, particularly in rural areas, due to heavy physical labor, non-ergonomic working postures, and limited access to health education. These conditions can reduce productivity, impair quality of life, and increase the risk of disability if preventive measures are not implemented early. Community-based health promotion programs that combine educational approaches with hands-on practice represent an effective strategy to enhance community knowledge and skills in preventing musculoskeletal problems. Furthermore, cross-national collaboration in community service initiatives can enrich learning methods and broaden perspectives in delivering health education. This community service program aimed to provide health promotion to prevent musculoskeletal health problems in rural areas by involving students from Indonesia and Thailand. The program employed a pre- and post-intervention design to evaluate improvements in knowledge and skills among 20 participants in a rural community. The results demonstrated increased competency following student-led simulations, with correct responses rising to 95% in injury prevention, 90% in stretching and muscle strengthening, and 90% in the ability to identify populations vulnerable to musculoskeletal problems. Specifically, participants’ ability to perform back-strengthening exercises improved to a mean score of 4.10±1.02, indicating that direct demonstration of techniques had a significant impact. Participants also showed the highest level of confidence when performing upper-arm stretching exercises, with a mean score of 4.65±0.87, reflecting strong understanding among the participants. Another key finding revealed that video was the most preferred learning method, chosen by 55% of participants. The use of this learning medium has considerable potential to support musculoskeletal health promotion in rural communities. Overall, the program achieved its intended objectives and provides a replicable model for similar health promotion initiatives in other rural areas. These findings may inform future health promotion strategies by emphasizing the use of multimedia and experiential learning approaches in delivering education and enhancing skills within musculoskeletal health programs.